Critical Barriers to Successful Implementation of Earth-Abundant, Mn-Rich Cathodes for Vehicle Applications and Beyond: A Detailed Study of Low SOC Impedance. Issue 8 (6th August 2021) - Chen, Jiajun; Gutierrez, Arturo; Saray, Mahmoud Tamadoni; Yassar, Reza Shahbazian; Balasubramanian, Mahalingam; Wang, Yan; Croy, Jason R.
Abstract : Earth-abundant, sustainable cathode chemistries based on Mn are increasingly attractive for enabling a broader portfolio of cathode oxides. The well-known class of lithium- and manganese-rich cathodes still represents very viable options. However, despite the important work on understanding the mechanisms of voltage fade, hysteresis, and oxygen activity, relatively little attention has been given to understanding the impedance characteristics of these electrodes. In particular, an anomalous rise in area specific impedance at lower states of charge, as well as overall impedance rise and surface damage due to electrolyte interactions, represent critical barriers to implementation. This work presents a comprehensive study of impedance behavior in cobalt-free, lithium- and manganese-rich electrodes. The use of a robust surface treatment allows for long-term behavior to be probed in the absence of surface damage, capacity loss, and impedance rise due to electrolyte interactions. The anomalous rise in impedance could not be correlated to surface changes, or surface phase formation, but could be directly correlated with the bulk processes of voltage fade and voltage hysteresis. The activated material can be explained as a percolating network of higher-voltage, layered-type sites having facile Li diffusion. Interspersed throughout this network are lower-voltage, disordered sites that represent a significant barrier.